Aplikasi Desa Wisata Berbasis Android - Mahendra, Ida Bagus Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Village tourism is a form of integration between attractions, accommodation and supporting facilities that are presented in a structure of community life that integrates with applicable procedures and traditions. Indonesia has many rural areas which have some special characteristics that are worthy of being tourist destinations. Unique activities that do not exist in other places become an advantage of Indonesia with its diversity of arts and culture. Appropriate technology can help to provide information that is easier and more interesting.The Android-based Tourism Village application was developed based on the latest technology expected to overcome the internal problems of tourism villages in Indonesia, especially in terms of marketing to the outside world and can be one of the platforms in increasing the income of people living in Tourism Villages.